Pengaruh motivasi, kepuasan kerja, dan kepemimpinan terhadap kinerja karyawan pada PT. XYZ - Nikolas Ivan Waskita Adiyasa; Windayanti Windayanti (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2019)
This study aims to determine whether there is influence between motivation, job satisfaction, and leadership on employee performance of PT XYZ. This research uses a quantitative approach by distributing questionnaires to 45 employees of PT XYZ. The result shows that motivation and leadership have a significant effect on employee performanc, but job satisfaction variable has no significant effect. The implication of this finding is that increasing leadership capacity and motivation simultaneously can be determinants of employee performance.